POLICY ANALYSIS MATRIX FOR THE ESSENTIAL CEREAL CROPS VARIETIES (RICE BUHOOTH 1, AND CORN SYNTHETIC GENOTYPE BAGHDAD 3) (STUDY CASE) IN IRAQ FOR THE YEAR 2012 - & et al., Lateef (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The objective of this research was to analyze the economic impact of government intervention in the essential cereal crops for (Rice Buhooth1, and Synthetic genotype Baghdad3) by comparing the social price and private prices through adopting policy analysis matrix approach PAM and the derived parameters from it .The research was divided into two chapters; the first chapter was about field counting for the policy analysis matrix PAM and measuring the implications of the government intervention on the Rice Buhooth1. The second chapter was about explaining the field counting for policy analysis matrix PAM and measuring the implications of the government intervention impact on the second synthetic genotype Baghdad3.The research found a set of results, the most important result showed that the value of profitability coefficient was about 3.69, this indicates that the rice crop production system for the Rice Buhooth 1  takes advantage of the adopted government policy in that year, which means that there is governmental support for the product. In addition, domestic resource cost coefficient value which was about 0.72 indicates that there is comparative advantage for the Rice Buhooth 1  for the year 2012. The values of the nominal and effective protection coefficient were about 1.74 and 1.59 respectively; the value of the first factor indicates that there is governmental support for the domestic producer for the above, while the second factor indicates that the domestic producer will obtain greater returns in the investment of its resources in the existence of the government intervention from its absence. Regarding the Synthetic genotype Baghdad3, the value of profitability coefficient was about  1.75  which means that there is governmental support for the product. The domestic resource cost coefficient value was about 0.24 which indicates that there was comparative advantage for the mentioned above for the year 2012. The values of the nominal and effective protection coefficient were about 1.48 and 1.56 respectively; the value of the first factor indicates that there is governmental support for the domestic producer for the above, while the second factor indicates that the domestic producer will obtain greater returns in the investment of its resources in the existence of the government intervention from its absence. Finally, it is highly recommended that support should be increased for the varieties that the country has greater comparative advantage in order to improve the utilization of available resources and reduce wasted resources. Moreover, similar studies should be done in the future by other researchers to major cereal crops varieties at the country level in order to do comparison between them to set a mechanism for the government intervention policy in the main crop prices in the country which help both the local producer and agricultural investor in directing its resources properly.